TECHNIQUES TO EVALUATE AND COMBINE CULTURAL ERRORS IN UZBEK AND ENGLISH - Saparova Dilafruz Muxiddin qizi; G. Ro’ziyeva (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract This article explores effective techniques for evaluating and combining cultural errors in Uzbek and English communication. Cultural differences often lead to misunderstandings, particularly when language nuances, idiomatic expressions, or societal norms are misinterpreted. The paper highlights key methods such as comparative cultural analysis, error categorization, and cross-cultural training to minimize and address these errors. Practical solutions are proposed to bridge cultural gaps, fostering effective communication and mutual understanding between Uzbek and English speakers in various social, educational, and professional contexts.